Sexual citizenship and disability : understanding sexual support in policy, practice and theory - Bahner, Julia (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"What does 'sexual citizenship' means in practice for people with mobility impairments who may need professional support to engage in sexual activity? This book explores this subject through empirical investigation based on case studies conducted in 4 countries- Sweden, England, Australia and the Netherlands- and develops the abstract notion of 'sexual citizenship' to make it practically relevant to disabled people, professionals in disability services and policy makers. Through a cross-national approach, it demonstrates the variability of how sexual rights are understood and their culturally-specific nature. It also shows how the personal is indeed political: states' different policy approaches change the outcomes for disabled people in terms of support to explore and express their sexualities. By proposing a model of sexual facilitation that can be used in policy development, to better cater to disabled service users' needs as well as furthering the theoretical understanding of sexual rights and sexual citizenship, this book will be of interest to professionals in disability services and policy makers as well as academics and students working in the following subject areas: Disability Studies, Sociology, Social Policy, Sexuality Studies/Sexology, Social Work, Nursing, Occupational Therapy and Public Health"--
OCLC-licensed vendor bibliographic record.
Keywords: Sex instruction for people with disabilities -- Case studies; People with disabilities -- Sexual behavior -- Case studies; SOCIAL SCIENCE / Social Work; SOCIAL SCIENCE / Handicapped